Postural control: differences between youth judokas and swimmers - Itamar, N.; Schwartz, D.; Melzer, I. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: Specific physical training may improve balance control. This study aims to explore the underlying mechanisms of balance control in young Judokas compared with the type of training that does not require balance skills (swimming). Methods: Nine young judokas and nine age-gender matched swimmers (10.5-17-year-old) participated in the cross-sectional study. Postural Stability was collected using force platform during 10 upright standing trials in each of the three conditions: eyes open, eyes closed, and standing on foam. The force platform data were sampled at a frequency of 100 Hz, than analyzed using summary statistics and Stabilogram-Diffusion Analysis (SDA) for mediolateral (ML) and anteroposterior (AP) directions. Results: The results show that Judokas have better stability than swimmers in eyes closed condition but lower stability while standing on foam, with no significant differences in eyes open condition. The long-term effective diffusion coefficient of the SDA was significantly lower in judokas in all three postural task conditions. Conclusions: The results show that Judokas are able to cope with momentary loss of vision better than swimmers, and less able to compensate reduction in somatosensory cutaneous sensation (e.g. standing on foam). These results suggest that judokas are less visually dependent relying on their sensorimotor system compare with swimmers. judokas have a more effective closed-loop balance control thus able to minimize their sway. It seems that training includes unexpected perturbations of the postural control system, emphasizing sensorimotor adaptabilities.